Graffiti on the walls: an action research plan on how making authentic opportunities for student composition helps Latin 1 comprehension. Issue 39 (2019) - Holke, Jacob
Abstract : With the changes made in the new US Standards for Classical Language Learning, pedagogy needs to develop to better meet the updated standards for student learning. One of the major changes is that reading Latin is no longer the sole pursuit of a high school Latin class (Standards, 2017; Natoli, 2018). The new standards recognise that students learn in diverse ways and that students need to learn about and interact with the cultures they are studying.